Measurement on $$π ^ + π ^ - π ^0 π ^0 $$ , $$π ^ + π ^ - π ^ + π ^ - π ^0 $$ , $$π ^ + π ^ - π ^ + π ^ - π ^0 π ^0 $$ , $$π ^ + π ^ - π ^ + π ^ - π ^ + π ^ - $$ production cross-sections in e+e− annihilation at (1.45÷1.80) GeV c.m. Energyproduction cross-sections in e+e− annihilation at (1.45÷1.80) GeV c.m. Energy - B. Esposito; A. Marini; G. Piano-Mortari; F. Ronga; M. Nigro; L. Pescara; R. Bernabei; S. d'Angelo; P. Monacelli; M. Moricca; L. Paoluzi; R. Santonico; et al. (Lettere Al Nuovo Cimento Series 2, 1981)
Objective This study estimated the prevalence of problematic smartphone use (PSU) among multicultural adolescents and examined its association with major mental health indicators. Methods We conducted a cross-sectional analysis of the 2020 Korea Youth Risk Behavior Web-based Survey, which included 1,065 adolescents from multicultural families. PSU was assessed via the validated Korean version of the Smartphone Overdependence Scale. The mental health variables included perceived stress, loneliness, anxiety symptoms, and suicidal ideation, plans, and attempts. Multivariate logistic regression models were used to identify factors associated with PSU. Structural equation modeling (SEM) was applied to evaluate the direct associations between PSU and mental health outcomes and to test the moderating effects of key demographic and psychosocial factors. Results The prevalence of PSU among multicultural adolescents was 26.2%. Compared with adolescents not in the PSU group, those in the PSU group more frequently reported high perceived stress, frequent loneliness, elevated anxiety symptoms, and suicidal ideation. In adjusted models, PSU was independently associated with higher odds of stress, loneliness, anxiety, and suicidal planning, as well as lower academic achievement. The SEM findings supported significant associations between PSU and multiple mental health indicators, with some associations being stronger among girls, adolescents from lower-income households, and those experiencing higher levels of stress or loneliness. Conclusion Among Korean multicultural adolescents, PSU is common and is associated with multiple adverse mental health and poorer academic self-perceptions. These findings underscore the importance of culturally sensitive strategies that address both digital media use and psychosocial well-being among multicultural adolescents.